Description of Nurse's Knowledge, Attitude and Competence in Social Media - Muhammad Hardiansyah; Yulastri Arif; Zifriyanthi Minanda Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe nurses' knowledge, attitude, and competence in using social media. The research method used is quantitative descriptive research. The results showed that the average respondent's understanding of social media was 5.87, with a minimum score of 1 and a maximum score of 11 out of a total score of 0-25. The average altitude of respondents to social media is 80.39, with a minimum score of 64 and a maximum score of 96 out of a total score of 25-125. The average nurse competency in social media is 68.19, with a minimum score of 50 and a maximum score of 94 out of a total score of 30-150. In conclusion, nurses' knowledge, attitude, and competence in social media still need to be added to the expected total score. Keywords: Competence, Social Media, Knowledge, Nurse, Attitude